40Ar/39Ar ages for deep (~3.3 km) samples from the Hawaii Scientific Drilling Project, Mauna Kea volcano, Hawaii - Jourdan, Fred; Sharp, Warren; Renne, Paul (American Geophysical Union, 2012)
The Hawaii Scientific Drilling Project recovered core from a 3.5 km deep hole from the flank of MaunaKea volcano, providing a long, essentially continuous record of the volcano’s physical and petrologicdevelopment that has been used to infer the chemical and physical characteristics of the Hawaiian mantle plume. Determining a precise accumulation rate via 40Ar/39Ar dating of the shield-stage tholeiites, which constitute 95–98% of the volcano’s volume is challenging. We applied 40Ar/39Ar dating using laser- and furnace-heating in two laboratories (Berkeley and Curtin) to samples of two lava flows from deep in the core (~3.3 km). All determinations yield concordant isochron ages, ranging from 612 +/- 159 to 871 +/- 302 ka (2delta; with P = 0.90). The combined data yield an age of 681 +/- 120 ka (P = 0.77) for pillow lavas near the bottom of the core. This new age, when regressed with 40Ar/39Ar isochron ages previously obtained for tholeiites higher in the core, defines a constant accumulation rate of 8.4 +/- 2.6 m/ka that can be used to interpolate the ages of the tholeiites in the HSDP core with a mean uncertainty of about 83 ka. For example at ~3300 mbsl, the age of 664 +/- 83 ka estimated from the regression diverges at the 95% confidence level from the age of 550 ka obtained from the numerical model of DePaolo and Stolper (1996). The new data have implications for the timescale of the growth of Hawaiian volcanoes, the paleomagnetic record in the core, and the dynamics of the Hawaiian mantle plume.